The Clinical Consistency and Utility of ICD-11 Diagnostic Guidelines for Gaming Disorder: A Field Study Among the Chinese Population - Ma, Chenyi; Wang, Zhe; Li, Chuanwei; Lu, Jing; Long, Jiang; Li, Ruihua; Wu, Qianying; Jiang, Haifeng; Du, Jiang; Li, Runji; Wang, Peiyan; Ma, Limin; et al. (Frontiers in Psychiatry, 2021)
【Abstract】 Purpose: As a new category proposed in ICD-11, the reliability and clinical utility of ICD diagnostic guidelines for gaming disorder(GD) in the Chinese population have not been studied. The purpose of this field study is to clarify the reliability, clinical utility, and cultural applicability of ICD diagnostic guidelines for GD in China, and its comparability to Internet gaming disorder(IGD) in DSM-5. Methods: Participants included 21 pair clinical raters consisting of 7 psychiatrists and 200 gaming players aged from 15-18 years old with different risk levels of internet addiction based on the scores of Young’s Internet Addiction Test. Each participant received a semi-structured face-to-face interview by paired clinical raters at the same time. Then clinical raters made the diagnosis and filled the clinical utility questionnaire independently according to the diagnostic guidelines for gaming disorder in both ICD-11 and DSM-5. Results: The diagnostic consistency coefficient (kappa value) between the paired clinical raters was 0.545(0.490-0.600, p<0.001), and 0.622(0.553-0.691, p<0.001) for ICD-11 and DSM-5 diagnostic guidelines for gaming disorder. The diagnostic consistency was 0.847(0.814-0.880, p<0.001) between GD in ICD-11 and IGD in DSM-5. Meanwhile, 86.7% of responses agreed ICD-11 diagnostic guidelines for GD provided enough detailed implementation characteristics and showed good overall clinical applicability (86.0%), specificity (94.4%), usefulness (84.1%), as well as acceptable cultural adaptation (74.8%). GD in ICD-11 was slightly more accepted than IGD in DSM-5 (p<0.001), while the clinical efficiency of ICD-11 was inferior to DSM-5 (p<0.001). Conclusion: This study indicates the ICD-11 diagnostic guidelines for GD have acceptable clinical reliability and high consistency with IGD in DSM-5. Its clinical applicability and cultural adaption are comparable with DSM-5. Although the guidelines still need to be adjusted for better implementation in China, this is already a great step committed to reducing the serious consequences caused by excessive gaming behaviors through effective identification and normative diagnosis, especially for adolescents.